KAJIAN PENGEMBANGAN AGRIBISNIS KOMODITAS UNGGULAN BUAH-BUAHAN DI KABUPATEN KUBU RAYA - JUARSYAH, RENDRA; MUANI, ANI; SUYATNO, ADI (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
The purpose of this research are : 1). To determine the high priority of prime commodity of fruits to develop in Kubu Raya regency 2). To formulated the alternative strategy to develop agribusiness prime commodity of fruits in Kubu Raya regency 3).To formulated the direction of estate crops commodities development in Kubu Raya regency.This research has taken for six months. Data using primary data and sekunder. The respondents determined by using purposive sampling technique The method of this research was descriptive method by means of survey. Primary data was collected through questionnaire and depth-interviews. The samples were purposively taken, consists of the expert and stakeholders in Kubu Raya regency. Data analysis carried out by Location Quotient (LQ) analysis, using descriptive analysis and supported by Internal Factor Evaluation Matrix, External Factor Evaluation Matrix, TOWS (Threats, Opportunities, Weakness, Strength) matrix and scoring Analysis.The results showed, the internal factors, which tobe the strengths were: land resource, strategic location, local government policies, and existence of traders and seed breeders. On contrary, the weakness factors were: low technological use in post-harvest and product processing, fruits business management, institutional (farmer groups), and capital access. While, the external factors those to be opportunity were:promotion program in national and international events, increase in fruits demand, decentralization, horticulture development policies from Ministry ofAgriculture. Nonetheless, the treats factors were: fluctuated fruits’ prices,coordination among government agencies, trade liberalization and globalization, and quality standards systemThe seven strategy alternative are : 1). The increase production of fruits commodity 2). The developing area and prime commodities center 3). The empowering farmer institution 4). The developing of fruits management 5). The developing of agro industries 6). Optimizing the coordination among the involved agencies 7). Increasing the human resources competence. Keywords: Agribusiness, Prime commodities, Fruits, LQ, IFE, EFE, SWOT